Exercise Alters Gait Pattern but Not Knee Load in Patients with Knee Osteoarthritis. (20th September 2016) - Chang, Ssu-Yu; Lin, Yi-Jia; Hsu, Wei-Chun; Hsieh, Lin-Fen; Lin, Yuan-Hsiang; Chang, Chao-Chin; Chou, You-Cai; Chen, Li-Fei
Abstract : Six female patients with bilateral medial knee OA and 6 healthy controls were recruited. Patients with knee OA received a 6-week physiotherapist-supervised and home-based exercise program. Outcome measures, including the Western Ontario and McMaster Universities Arthritis Index and Short Form-36 Health Survey as well as objective biomechanical indices were obtained at baseline and follow-up. After treatment, no significant difference was observed in the knee abductor moment (KAM), lever arm, and ground reaction force. We, however, observed significantly improved pain and physical function as well as altered gait patterns, including a higher hip flexor moment and hip extension angle with a faster walking speed. Although KAM was unchanged, patients with bilateral knee OA showed an improved walking speed and altered the gait pattern after 6 weeks of supervised exercise. This finding suggests that the exercise intervention improves proximal joint mechanics during walking and can be considered for patients with bilateral knee OA. Non-weight-bearing strengthening without external resistance combined with stretching exercise may be an option to improve pain and function in individuals with OA who cannot perform high resistance exercises owing to pain or other reasons.